Teachers' Perspectives on Primary School Students' Speaking and Presenting Skills: A Survey Study - Adrias; Mansurdin; Yunisrul; Agus Ruswandi; Fadhilah Majid (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2026)
Abstract: Speaking and presenting are learning outcomes that present greater challenges than other elements as they require students to possess both adequate verbal proficiency and psychological readiness. This study aims to describe teachers' perceptions of student achievement in speaking and to identify the factors perceived to influence these outcomes. A quantitative survey method was employed, utilizing questionnaires for data collection. The respondents consisted of 161 fifth and sixth-grade elementary school teachers in Padang City, selected through multistage random sampling. Data were analyzed using descriptive statistics. The results indicate that the overall achievement level of speaking and presenting in Phase C is 77.90%, categorized as "High". The highest achievement was found in students' post-learning confidence at 81.57% (Very High), while the lowest achievement was in the ability to organize a presentation with a clear structure (introduction, body, and conclusion), which only reached 69.57% and was categorized as "Moderate". Abstrak: Berbicara dan mempresentasikan merupakan salah satu hasil belajar yang lebih sulit dibandingkan unsur-unsur lain, karena keduanya menuntut siswa untuk memiliki kemampuan verbal yang memadai serta kesiapan psikologis. Penelitian ini bertujuan untuk menggambarkan persepsi guru terhadap pencapaian siswa dalam berbicara serta mengidentifikasi faktor-faktor yang dianggap memengaruhi hasil belajar tersebut. Metode survei kuantitatif digunakan dalam penelitian ini, dengan memanfaatkan kuesioner sebagai alat pengumpulan data. Responden terdiri dari 161 guru sekolah dasar kelas lima dan enam di Kota Padang, yang dipilih melalui pengambilan sampel acak bertahap. Data dianalisis menggunakan statistik deskriptif. Hasilnya menunjukkan bahwa tingkat pencapaian keseluruhan dalam berbicara dan mempresentasikan pada Fase C adalah 77,90%, yang dikategorikan sebagai "Tinggi". Pencapaian tertinggi ditemukan pada kepercayaan diri siswa pasca pembelajaran sebesar 81,57% (Sangat Tinggi), sedangkan hasil terendah terdapat pada kemampuan menyusun presentasi dengan struktur yang jelas (pendahuluan, isi, dan kesimpulan), yang hanya mencapai 69,57% dan dikategorikan sebagai "Sedang".